On Bad Weather: Heidegger, Arendt, and Political Beginnings - Vega, Facundo Hernan (2020)
This essay restages Arendt’s Auseinandersetzung with Heidegger regarding ‘political beginnings’. Sketching Heidegger’s exceptionalist account of ‘new beginnings’ and Arendt’s dispute with him in relation to the tension between the spheres of ‘philosophy’ and ‘politics’, I trace her position about ‘political founding’. I claim that Arendt invites us to recognize the ‘principle of an-archy’ innate to ‘political beginnings’, which cannot be absorbed by exceptionalist invocations of the ‘history of Being’.